I left my sneakers in Dimension X - Coville, Bruce; Coville, Katherine (New York : Aladdin Paperbacks, 2002)
Rod and his bratty cousin Elspeth are snatched into another dimension by the monstrous alien Smorkus Flinders.
"A Rod Allbright alien adventure"--Cover.
4.9
3-6
3-6
School Library Journal
Booklist
Keywords: Extraterrestrial beings -- Fiction; Science fiction; Extraterrestrial beings -- Fiction; Science fiction